Immunity system dysfunction caused by insomnia and methods of treatment - Augustynowicz, Kinga; Szymańska, Ewa; Ostaszewska, Sandra; Świąder, Kinga; Chrzanowski, Jakub; Morawski, Przemysław; Pactwa, Filip; Popińska, Zuzanna; Łoginoff, Jan (Journal of Education, Health and Sport, 2023)
Introduction: Sleep is a very important part of human health. Research over the past several years has shown that sleep disorders such as insomnia can affect the risk of infectious diseases. This review describes the immunocompromising mechanisms of insomnia and the consequences associated with this disorder. This review also includes treatment methods. Material and methods: The work was based on the articles published in PubMed, medical books and websites. Results: Insomnia has an influence in the markers of inflammation and there are few methods of treating insomnia. Conclusions: Sleep influences the two primary effector systems which in turn regulate immune responses. Sleep disturbance like insomnia increases the risk of infectious diseases. Treatment can lower the markers of inflammation and helps relieve the symptoms of insomnia.